3(6-x)=27

Simple and best practice solution for 3(6-x)=27 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(6-x)=27 equation:


Simplifying
3(6 + -1x) = 27
(6 * 3 + -1x * 3) = 27
(18 + -3x) = 27

Solving
18 + -3x = 27

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-18' to each side of the equation.
18 + -18 + -3x = 27 + -18

Combine like terms: 18 + -18 = 0
0 + -3x = 27 + -18
-3x = 27 + -18

Combine like terms: 27 + -18 = 9
-3x = 9

Divide each side by '-3'.
x = -3

Simplifying
x = -3

 

See similar equations:

| 10+2r=8 | | X+3(x+4)=20 | | 18+(2x+9)-(7x-10)=(16-3x)-(10+7-5)-8(9x+4)+11-7 | | -2(6n-5)=-26 | | 22+(-22)= | | 13=1+4s | | 4=9y-4 | | X+6-9x=2-x-5 | | -4-2= | | 2t+7=-1 | | 3(3x-4)=x+3 | | 3-(-8)= | | 17=8x+12 | | X+3=4(4x-6) | | -5(-11x-4)+3(x-5+6)-(10x-5)=7(4x-5+6)+2x-10+(25-10)+4-13 | | x(4x-9)=13 | | 4w-5=16 | | -3+5n=8 | | -x+4x-2(x-8+9)-16+x-5=4x-5+6(4x-5+9)+18-3x | | c+d=e | | 7t+8=-5 | | -3g-8=2 | | x+y=5 | | n-11+5=-4(n+3)-9(8-2n) | | 7x+3y=1 | | 7y+3x=1 | | -8x+2=-3 | | 8x-3=11-6x | | 3x=-9+6 | | 3x=6+-9 | | 15x=10x-30 | | 8x+2x=15x-10 | | 4y+y+1=7(y-1) | | w+3=w+6 | | 8z=4(2z+1) | | 22x+70=17x-95 | | 12y+6=6(2y+1) | | 11a+9=4a+30 | | 8+5x-6=37 | | 3x+12=-10 | | 3(5-x)=2x-x | | x-2.8=1.6 | | 2(x+x+3)=x+2+18 | | 7-5x=2(4+x) | | 5x-7=2(4+x) | | 3(x-5)=2x-x | | 85=21+4n | | 4x-3=4(5-x) | | 3(x+2)-4(3+2x)=0 | | 2(x+x+2)=x+1+18 | | 10x-5y=95 | | 60=21+3t | | 4(2m+5)=3m-5 | | 11w+2(w+1)=5w-6 | | .5(12n-2)=5n-7 | | -.75(8x-12)=5x-2 | | 2y+18=12-6(y+7) | | 5t-5=5t+7 | | .33(6x+3)=2x-5 | | .2(15z-5)=4(4z+1) | | 5+5= | | (3y-11)=(y+19) | | (3y-11)+(y+19)=90 | | 16x-19=113-6x | | 8+6p=p+p |